Viabilidade da corrente aussie durante aplicação da carboxiterapia no tratamento para celulite: uma série de casos - Tozzi, Mariele Beatriz (Universidade Federal de São Carlos, 2022)
Introduction: Carboxytherapy consists of the administration of carbon dioxide (CO2) subcutaneously. The application is done through needles, which can generate local pain, which is considered the main limiting factor in clinical practice. The Aussie current is indicated for pain control, and as it is a medium frequency current, it is considered that it can reach deeper tissues and may be a promising current in the relief of pain in painful procedures, such as pain caused by carboxytherapy. Objective: To investigate the feasibility of the Aussie current over three sessions during the application of carboxytherapy in the treatment of cellulite. Methods: This is a case series aimed at assessing pain intensity and increasing current amplitude. Pain intensity was assessed using the Numerical Pain Scale (END), being measured by each quadrant that received a maximum of two punctures. With this, the average of pain intensity was performed by quadrant and, later, by gluteal laterality that received the intervention. At the end of the three sessions performed, the averages found between them were compared. The current amplitude was recorded in mA at the beginning and end of each session. In addition, it was adjusted throughout the therapeutic procedure and compared between the three sessions performed. The research was carried out in 25 women, between 18 and 49 years old, with no previous experience with carboxytherapy therapy, with presence of moderate and/or severe cellulite in the gluteal region, according to the Cellulite Severity Scale (CSS). For the intervention, the depressions of the skin with cellulite were demarcated and the delimitation of the gluteal area was performed for the infiltration of CO2 in the subcutaneous tissue, whose volume of gas infused by puncture was 50 ml. The Aussie current parameters were: carrier frequency of 4 kHz, phase duration of 125 μs (pulse duration = 250 μs), duty cycle of 20% (burst duration of 4 ms), modulation frequency of 100 Hz and amplitude gradually adjusted for maximum tolerable sensation. Results: The pain intensity assessed showed a considerable reduction over the three sessions and the current amplitude increased. Conclusion: It is concluded that the use of the Aussie current during the application of carboxytherapy was feasible. Pain intensity decreased over the three sessions and current amplitude showed a gradual increase between sessions.
Viability of the Aussie current during the application of carboxytherapy in the treatment of cellulite: a case series
Keywords: Dor; Carboxiterapia; Saúde da mulher; Celulite; Pain; Carboxytherapy; Women's health; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL